2022
DOI: 10.3389/fgene.2022.905988
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 serves as a novel diagnostic and prognostic biomarker and is closely correlated with immune microenvironment in three types of cancer

Abstract: Background: Toll-like receptor 3 (TLR3) plays an important role in both innate and adaptive immunity, but the prognostic value of TLR3 in heterogeneous tumors and the correlations between TLR3 expression and immune infiltration of heterogeneous tumors remain unclear.Methods: We investigated the expression of TLR3 in a variety of tumors and focused on the diagnostic and prognostic values of TLR3 in kidney renal clear cell carcinoma (KIRC), pancreatic adenocarcinoma (PAAD) and brain lower grade glioma (LGG) by G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…TLR3 (Toll-like receptor 3) is a member of the TLR family, which mediates the transcription induction of type I interferon, pro-in ammatory cytokines and chemokines 42 , and its primary function is in the activation of the innate immune system in the process of anti-virus 43,44 . A recent bioinformatic study indicated that TLR3 can be a prognosis biomarker for many types of cancers 45 . In human non-small-cell lung cancer, TLR3 activation induces apoptosis 46 .…”
Section: Discussionmentioning
confidence: 99%
“…TLR3 (Toll-like receptor 3) is a member of the TLR family, which mediates the transcription induction of type I interferon, pro-in ammatory cytokines and chemokines 42 , and its primary function is in the activation of the innate immune system in the process of anti-virus 43,44 . A recent bioinformatic study indicated that TLR3 can be a prognosis biomarker for many types of cancers 45 . In human non-small-cell lung cancer, TLR3 activation induces apoptosis 46 .…”
Section: Discussionmentioning
confidence: 99%
“…These investigations have aimed to explore their associations with tumorigenesis, cancer progression, the modulation of tumor immune cell infiltration, the expression of immune checkpoints, and the upregulation of immunosuppressive genes. These molecules hold potential as future biomarkers for diagnosing and prognosing pancreatic adenocarcinoma, as well as serving as therapeutic targets for tumor immunotherapy [39][40][41][42][43][44].…”
Section: Prognostically Significant Tumor Immune Biomarkersmentioning
confidence: 99%
“…The toll-like receptors (TLRs) are critical in innate immunity as pattern recognition receptors. TLR3 is predominantly expressed in innate immune cells, such as dendritic cells (Figure S1), macrophages, and natural killer cells, which have been exploited extensively to enhance an antitumor immune response. Notably, TLR3 is highly expressed in many types of human solid tumors, including lung and breast cancer, oral cell squamous carcinoma, cervical carcinoma, and head and neck carcinoma. , This receptor is located in intracellular cytoplasm or endosomes and sensed double-stranded RNA (dsRNA) viruses, including polyriboinosinic:polyribocytidylic acid (poly (I:C)). TLR3 signaling activates NF-κB and upregulates the RHCG gene.…”
Section: Introductionmentioning
confidence: 99%
“…30−32 Notably, TLR3 is highly expressed in many types of human solid tumors, including lung and breast cancer, oral cell squamous carcinoma, cervical carcinoma, and head and neck carcinoma. 33,34 This receptor is located in intracellular cytoplasm or endosomes and sensed double-stranded RNA (dsRNA) viruses, including polyriboinosinic:polyribocytidylic acid (poly (I:C)). 35−37 TLR3 signaling activates NF-κB and upregulates the RHCG gene.…”
Section: Introductionmentioning
confidence: 99%